Evaluation of high temperature rheological performance of polyphosphoric acid-SBS and polyphosphoric acid-crumb rubber modified asphalt. (1st November 2021) - Ma, Feng; Li, Chen; Fu, Zhen; Huang, Yue; Dai, Jiasheng; Feng, Qiao
Abstract: This study explores the effects of polyphosphoric acid (PPA) on the rheological performance of styrene butadiene styrene (SBS) and crumb rubber (CR) modified asphalt binders at high temperatures. Four PPA concentrations were selected: 0.4%, 0.8%, 1.2%, and 1.6% by weight of virgin asphalt, and one SBS modified binder with 5% SBS by weight was used as a reference binder. Laboratory tests were performed to simulate short-term and long-term aging. Temperature sweep, frequency sweep, multiple stress creep recovery (MSCR) and repeated creep recovery (RCR) tests were also conducted to investigate the rheological properties of asphalt binders (i.e., PPA-SBS, PPA-CR and SBS modified). Fourier transform infrared spectroscopy (FTIR) test was used to study the chemical reaction of modifiers in the asphalt. Results showed that PPA improved the asphalt's resistance to permanent deformation and enhanced their elastic recovery behavior. Moreover, results of the rutting factor (G*/sinδ), complex modulus (G*), zero shear viscosity (ZSV), recovery percentage (R), non-recoverable compliance (Jnr) and viscous stiffness modulus (Gv) suggested that PPA-SBS had the best modification effects, followed by PPA-CR. Besides, results of the viscosity-temperature susceptibility (VTS) indicated that the additives decreased the temperature susceptibility of composite modified asphalt binders. PPA modified asphalt binder had good anti-aging behavior when the PPA content was no <0.8% of the virgin asphalt. Additionally, CR-modified asphalt binder with PPA additives exhibited the most improved aging and loading resistance.